The Influence of Competence and Information Technology Utilization on Employee Performance with Organizational Culture as a Moderating Variable at Amanjiwo Resort in Magelang - Amanda, Faradilla Eka; Probosari, Ninik (Universitas Mercu Buana, 2024)
This study aimed to determine and analyze the Effect of Human Resource Competence and Information Technology Utilization on Employee Performance with Organizational Culture as a Moderation Variable at Amanjiwo Resort in Magelang.. This type of research is quantitative research. The data in this study are primary and secondary data in the form of questionnaires given to 91 respondents and the results of interviews with the Human Resource Manager of Amanjiwo Resort. The population of this study were all employees at Amanjiwo Resort, totaling 117 people. The sampling technique used was a random sampling technique with cluster random sampling with a sample of 91 people. The method used is the Structural Equation Model (SEM) method with the help of SmartPLS 4 software. The analysis technique used is the PLS SEM method in the form of outer model analysis and inner model analysis. The results of this study indicate tha t: 1.Human resource competence has a positive effect on employee performance at Amanjiwo Resort, 2.Utilization of information technology has a positive effect on employee performance at Amanjiwo Resort, 3.Organizational culture does not moderate the influence of human resource competence on employee performance, 4.Organizational culture does not moderate the effect of using information technology on employee performance.